SURFACE LINGUISTIC ERRORS IN ORAL PRESENTATION: A CASE STUDY OF SECONDARY STUDENTS IN 3T REGION KUPANG TIMUR - Bajo, Simforianus Mario; Lomi, Aplonia Nelci Ke; Lake, Floribertha (Universitas PGRI Palembang, 2025)
This study examines the types and frequency of surface linguistic errors in English oral storytelling by junior high school students from the 3T (frontier, outermost, disadvantaged) region of Kupang Timur. Using a quantitative approach, data were collected from 15 students and analyzed through Dulay et al.’s Surface Strategy Taxonomy, with error analysis following Ellis’s framework: identification, description, explanation, and evaluation. The results show that omission errors were most frequent (47%), followed by addition (27%), misformation (20%), and misordering (6%). Frequent mistakes included the omission of “to be” verbs and possessive apostrophes, indicating limited mastery of basic English grammar in spoken form. These findings highlight the specific grammatical challenges faced by learners from remote, under-resourced areas. The study offers valuable implications for English language instruction, suggesting the need for targeted teaching strategies and curriculum development that address the unique needs of students in 3T regions. By focusing on an underrepresented group in Indonesian educational research, this study provides new insights into how linguistic background and educational access shape oral language proficiency, advocating for more inclusive and context-sensitive language teaching practices.